The Expansion of Lignocellulose Biomass Conversion Into Bioenergy via Nanobiotechnology - Sankaran, Revathy; Markandan, Kalaimani; Khoo, Kuan Shiong; Cheng, Chin Kui; Ashokkumar, Veeramuthu; Deepanraj, B.; Show, Pau Loke (Frontiers in Nanotechnology, 2021)
Converting lignocellulosic biomass to sugar is a complicated system involved in the bioconversion process. There are indeed a variety of techniques that have been utilized in the bioconversion process consisting of physical, chemical, and biological approaches. However, most of them have drawbacks when used on a large-scale, that includes the high cost of processing, the development of harmful inhibitors and the detoxification of the inhibitors that have been produced. Those constraints, taken together, hinder the effectiveness of current solutions and demand for the invention of a new, productive, cost-effective, and environmentally sustainable technique for LB processing. In this context, the approach of nanotechnology utilizing various nanomaterials and nanoparticles in treating lignocellulose biomass and bioenergy conversion has achieved increased interest and has been explored greatly in recent times. This mini review delves into the application of nanotechnological techniques in the bioconversion of lignocellulose biomass into bioenergy.